Nano-scale surface of ZrO2 ceramics achieved efficiently by peanut-shaped and heart-shaped SiO2 abrasives through chemical mechanical polishing. Issue 9 (15th June 2020) - Xu, Lei; Lei, Hong
Abstract: Zirconia ceramics are regarded as the best development target for 5G mobile phone rear covers. However, it is necessary and urgent to improve the surface quality and processing efficiency of zirconia ceramics. Non-spherical silica abrasives were prepared by the KH550 induction method and were used in chemical mechanical polishing (CMP) of zirconia ceramics for the first time. While achieving low surface roughness of 1.9 nm, it has an efficient polishing rate of 0.31 μm/h which is superior to conventional abrasives. Silica particles are peanut-shaped and heart-shaped in the scanning electron microscopy image, and its distinctive morphology provides the possibility of its excellent polishing performance. X-ray photoelectron spectroscopy analysis shows that during the CMP process, silica abrasives and zirconia ceramic undergo a solid phase chemical reaction to form ZrSiO4 . At the same time, the contact wear model established in combination with the coefficient of friction indicates that the two-dimensional surface contact mode of non-spherical silica abrasives on the surface of zirconia ceramics greatly improves its mechanical effect.